Flow and fate of silver nanoparticles in small French catchments under different land-uses: The first one-year study. (1st June 2020) - Wang, Jia-Lan; Alasonati, Enrica; Tharaud, Mickaël; Gelabert, Alexandre; Fisicaro, Paola; Benedetti, Marc F.
Abstract: This study focused on surface waters from three small creeks, within the Seine River watershed, which are characterized by different land-uses, namely forested, agricultural and urban. Silver nanoparticles (Ag-NPs) in these waters were detected and quantified by single-particle ICPMS during one-year of monthly sampling. Their temporal and spatial variations were investigated. Ag-NPs, in the three types of surface water, were found to range from 1.5 × 10 7 to 2.3 × 10 9 particles L −1 and from 0.4 to 28.3 ng L −1 at number and mass concentrations, respectively. These values are in consistent with the very few previous studies. In addition, the role of factors driving process and potential sources are discussed with correlations between Ag-NPs concentrations and biogeochemical parameters, like dissolved organic carbon concentration and divalent cations concentrations. For the forested watershed NOM controls the stability (number and mass) of the Ag-NPs as recently observed in the field in lake water in Germany. In the case of the agricultural and urban watersheds major cations such as Ca would control the number and mass of Ag-NPs. Dilution processes are rejected as conductivity and Cl − ions do not show significant correlations with Ag-NPs or other major geochemical parameters. The specific exportation rates of Ag-NPs for artificial, agricultural and forested areas were calculated based on the monthly data for the full year and are equal to 5.5 ± 3.0, 0.5 ± 0.3 and 0.2 ± 0.2 gy −1 km −2, respectively. These data suggest a constant release of Ag-NPs from consumer products into freshwaters in artificial areas, for instance, from textiles, washing machines, domestic tap-water filters, outdoor paints. These first data of Ag-NPs fluxes in surface waters of France enlarge the very limited database of field measurements. Moreover, for the first time, the influence of time, land-use and aquatic geochemistry parameters on Ag-NPs in real natural water samples is reported. It is also helpful to further understand the fate and the process of Ag-NPs in natural waters, as well as to the ecotoxicity studies in real-world environment. Highlights: In a one-year study we report Ag-NPs occurrence in 3 watersheds with different land-uses. Concentrations range from 1.5 × 10 7 to 2.3 × 10 9 particles L −1 and from 0.4 to 28.3 ng L −1 . There is a strong correlation between DOC and Ag-NPs concentrations in forested water. An annual export rate of 2.3 ± 1.3 g/year/km 2 is obtained for the urban watershed. Agricultural and forested watersheds have smaller rates: 0.3 ± 0.3 g/year/km 2 .